Bibliometric analysis of hypospadias from 1998–2023 - Su, Dezhi; Li, Xiaowei; Li, Sha; Wang, Kun; Wu, Gangquan; Zhai, Guomin (Frontiers in Surgery, 2025)
IntroductionTo analyze the development trends and research hotspots in the field of hypospadias through bibliometric analysis.MethodsUtilizing three bibliometric mapping tools-bibliometrix R package, VOSviewer, and CiteSpace, we summarized the overview information of the retrieved literature. We conducted analyses on the co-occurrence and development trends of authors, institutions, countries, and keywords.ResultsA total of 3,647 hypospadias-related publications were included, with contributions from 14,633 authors. The keyword co-occurrence network identified seven clusters related to the diagnosis, pathophysiology, and treatment of hypospadias. Researchers have primarily focused on the genetic mechanisms of hypospadias, the role of environmental factors, surgical outcomes, anesthesia techniques, and patient satisfaction post-surgery. Emerging research hotspots include the precise selection of surgical flap sources, genomic alterations, and the correlation with syndromes related to disorders of sex development, all of which show strong potential for future breakthroughs.DiscussionBibliometric analysis provides a comprehensive understanding of the research hotspots and development trends in hypospadias, thereby enriching the field of hypospadias research.